The myth of the amateur : a history of college athletic scholarships - Smith, Ronald A. (Ronald Austin), 1936- (Terry and Jan Todd series on physical culture and sports., 2021)
"In this in-depth look at the heated debates over paying college athletes, Ronald A. Smith starts at the beginning: the first intercollegiate athletics competition--a crew regatta between Harvard and Yale--in 1852, when both teams received an all-expenses-paid vacation from a railroad magnate. This striking opening sets Smith on the path of a story filled with paradoxes and hypocrisies that plays out on the field, in meeting rooms, and in courtrooms--and that ultimately reveals that any insistence on amateurism is invalid, because these athletes have always been paid, one way or another. From that first contest to athletes' attempts to unionize and California's recent laws, Smith shows that, throughout the decades, undercover payments, hiring professional coaches, and breaking the NCAA's rules on athletic scholarships have always been part of the game. He explores how the regulation of student-athletes has shifted; how class, race, and gender played a role in these transitions; and how the case for amateurism evolved from a moral argument to one concerned with financially and legally protecting college sports and the NCAA. Timely and thought-provoking, The Myth of the Amateur is essential reading for college sports fans and scholars"--